ESG Strategies and Innovation Capabilities in Strengthening Corporate Performance in Indonesian Public Companies - Meiske Wenno; Rani Eka Arini; Dila Padila Nurhasanah (Westscience Press, 2026)
This study examines the influence of Environmental, Social, and Governance (ESG) strategies and innovation capabilities on corporate performance among Indonesian public companies. The increasing emphasis on sustainability and innovation has encouraged organizations to adopt responsible business practices while continuously enhancing their capacity to develop new products, services, and processes. This research employs a quantitative approach using a survey method. Data were collected from 125 respondents representing managerial and professional employees working in Indonesian public companies. The variables were measured using a five-point Likert scale, and data were analyzed using Statistical Package for the Social Sciences (SPSS) version 25. The analytical procedures included descriptive statistics, validity and reliability testing, classical assumption testing, multiple regression analysis, and hypothesis testing. The findings reveal that ESG strategies have a positive and significant effect on corporate performance, indicating that organizations implementing stronger environmental, social, and governance practices tend to achieve superior performance outcomes. Innovation capabilities also demonstrate a positive and significant effect on corporate performance, suggesting that firms with greater innovation capacity are more capable of improving competitiveness and organizational effectiveness. Furthermore, ESG strategies and innovation capabilities simultaneously exert a significant influence on corporate performance, explaining 47.3% of the variance in performance. The results suggest that sustainability-oriented strategies and innovation capabilities function as complementary strategic resources that enhance long-term organizational success. This study contributes to the literature on sustainability and strategic management by providing empirical evidence from Indonesian public companies and offers practical implications for managers seeking to strengthen corporate performance through integrated ESG and innovation initiatives.